Spiritual Fitness and Resilience A Review of Relevant Constructs, Measures, and Links to Well-Being - Yeung, Douglas (RAND Corporation, 2013)
This report is one of a series designed to support Air Force leaders in promoting resilience among its Airmen, civilian employees, and Air Force families. It examines the relationship between spiritual fitness and resilience, using key constructs found in the scientific literature: a spiritual worldview, personal religious or spiritual practices, support from a spiritual community, and spiritual coping.